Interpersonal Communication in Child Exploitation in Mojokerto - Melliana, Windika Anugra; M.I.A.H. Lailin; Ningsih, Masnia (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Some families strive to maintain open communication and support their children. Cultural and social factors also influence parental decisions, with some families viewing child labor as a reasonable economic contribution. The impact of child labor on family relationships varies, ranging from increased conflict to stronger bonds formed through shared struggles. This research highlights the importance of holistic interventions that are sensitive to the socio-cultural context in addressing child labor. Programs are needed to empower families economically, strengthen communication, and foster relationships to create an environment that supports the healthy and prosperous development of children. The study aims to understand the dynamics of communication within families whose children are involved in child labor in Balong Cangkring 2, Mojokerto. Using a case study analysis method, the results show that communication in child labor families involves making promises to their children about things they desire, which mothers use to persuade their children to work as instructed. At times, they also convey the family’s economic hardships that must be addressed through the employment of their children.